PEMANFAATAN WADUK BENING/ WIDAS SEBAGAI LOKASI PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) - Herwangga Satria Permana; Rintis Hadiani; Solichin Solichin (Jurnal Riset Rekayasa Sipil, 2019)
Electricity is a basic requirement in carrying out activities. However, over time, the electricity needs to increase but the availability of electricity is still stagnant. So that the necessary innovation of electricity generation. Solar power plants (PLTS) can be a solution to this problem. PLTS tends to require extensive land, therefore the idea of utilizing the reservoir as a PLTS location. In this penelitin selected Reservoir Bening / Widas as PLTS location. The calculation of the extent of the permit puddle needs to be done to find out how much PLTS design can be built. Furthermore, it is necessary to calculate the energy generated as well as economic feasibility analysis. The results of this study indicate that the area of permit inundation in the Bening / Widas Reservoir is 944893 m2 and PLTS which can be built as many as 20 modules with a design area of 1 module PLTS is 8000 m². The energy produced by 20 PLTS modules within 1 year is 19668.52 MWh.